The construction of a modified Typical Meteorological Year for photovoltaic modeling in India. (October 2017) - Murphy, Sean
Abstract: Typical Meteorological Years (TMY) provide a basis for modeling solar photovoltaics. Their use, however, assumes continued historical norms inconsistent with climate change. Modifying TMYs with Regional Climate Models (RCMs) responds to this issue and has applications in renewable energy evaluations. This paper provides perspective on using modified TMYs for solar resource assessments, offers methodological improvements, and analyzes the impacts of insolation and irradiation changes on photovoltaic performance. For Ahmedabad, India, a TMY is constructed from Indian Meteorological Department measurements and modified with two Regional Climate Models - REGCM4 and REMO 2009. For each modified TMY and baseline, the performances of three photovoltaic technologies (monocrystalline, polycrystalline, and double-junction amorphous silicon) are considered for 2015–2050. Increases in ambient temperature are found to have small (<1.0%) but increasing negative impacts on monocrystalline and polycrystalline performance through 2050. A less significant positive trend (<0.1%) was observed for double-junction amorphous silicon. Insolation adjustments for REGCM4 were excluded after an error analysis. Insolation changes from REMO 2009 projected a 4% decrease in photovoltaic output by 2050, but should be considered cautiously given concerns over cloud modeling. A sensitivity analysis of monthly insolation modifications on photovoltaic performance revealed the relative impact of insolation changes in different months. Highlights: Improved methodology for modifying horizontal and direct insolation for TMYs. Guidance on the appropriate use of monthly insolation values from RCMs. Guidance on interpretation and utility of annual insolation changes from RCMs. Decrease in module efficiency (0.6%) for mono and polycrystalline modules by 2050. Increase in efficiency (∼0.1%) is observed for double amorphous modules by 2050.